2014
DOI: 10.1007/s13277-013-1587-0
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty4 interferes with cell proliferation and migration of breast cancer-derived cell lines

Abstract: Sprouty proteins are modulators of mitogen-induced signal transduction processes and therefore can influence the process of cancerogenesis. In particular, Sprouty2 has been shown to have an important role in cancer development of many tumor entities including breast cancer. In this report, we investigated the role of Sprouty4 in breast cancer-derived cell lines. We have found that ectopic Sprouty4 expression inhibits cell proliferation of breast cancer cell lines independently of their endogenous expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 32 publications
4
34
0
Order By: Relevance
“…In agreement with an earlier study (27), the Spry4 levels were found to be differentially expressed depending on the subtype. The luminal subtypes of breast cancer demonstrated a decreased expression of the two Spry4 variants compared with the basal subtype.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with an earlier study (27), the Spry4 levels were found to be differentially expressed depending on the subtype. The luminal subtypes of breast cancer demonstrated a decreased expression of the two Spry4 variants compared with the basal subtype.…”
Section: Discussionsupporting
confidence: 92%
“…Spry proteins modulate the intensity and duration of the transmitted signals within such cascades, and therefore are important for the tumorigenesis of various tissues. Spry4 has been previously shown to fulfil a tumour suppressive function in lung (26) and breast (27) cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al reported that SPRY4 can serve as a suppressor of tumor cell motility and is down regulated by DNA methylation in human prostate cancer [6]. In addition, in human breast cancer, ectopic SPRY4 expression can inhibit cell proliferation and migration of breast cancer cell lines [7]. SPRY4 can also inhibit cell proliferation and migration in non-small cell lung cancer [8].…”
Section: Introductionmentioning
confidence: 99%